Glycoproteomic Probes for Fluorescent Imaging of Fucosylated Glycans in vivo - Sawa, Masaaki; Hsu, Tsui-Ling; Itoh, Takeshi; Sugiyama, Masakazu; Hanson, Sarah R.; Vogt, Peter K.; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2006)
Glycomics is emerging as a new field for the biology of complex glycoproteins and glycoconjugates. The lack of versatile glycan-labeling methods has presented a major obstacle to visualizing at the cellular level and studying glycoconjugates. To address this issue, we developed a fluorescent labeling technique based on the Cu(I)-catalyzed [3 + 2] cycloaddition, or click chemistry, which allows rapid, versatile, and specific covalent labeling of cellular glycans bearing azide groups. The method entails generating a fluorescent probe from a nonfluorescent precursor, 4-ethynyl-Nethyl-1,8-naphthalimide, by clicking the fluorescent trigger, the alkyne at the 4 position, with an azido-modified sugar. Using this click-activated fluorescent probe, we demonstrate incorporation of an azido-containing fucose analog into glycoproteins via the fucose salvage pathway. Distinct fluorescent signals were observed by flow cytometry when cells treated with 6-azidofucose were labeled with the click-activated fluorogenic probe or biotinylated alkyne. The intracellular localization of fucosylated glycoconjugates was visualized by using fluorescence microscopy. This technique will allow dynamic imaging of cellular fucosylation and facilitate studies of fucosylated glycoproteins and glycolipids.